The Posterior Parietal Cortex (PPC) Mediates Anticipatory Motor Control - Krause, Vanessa; Weber, Juliane; Pollok, Bettina (Brain stimulation, 2014)
Flexible and precisely timed motor control is based on functional interaction within a cortico-subcortical network. The left posterior parietal cortex (PPC) is supposed to be crucial for anticipatory motor control by sensorimotor feedback matching. Intention of the present study was to disentangle the specific relevance of the left PPC for anticipatory motor control using transcranial direct current stimulation (tDCS) since a causal link remains to be established. Anodal vs. cathodal tDCS was applied for 10 min over the left PPC in 16 right-handed subjects in separate sessions. Left primary motor cortex (M1) tDCS served as control condition and was applied in additional 15 subjects. Prior to and immediately after tDCS, subjects performed three tasks demanding temporal motor precision with respect to an auditory stimulus: sensorimotor synchronization as measure of anticipatory motor control, interval reproduction and simple reaction. Left PPC tDCS affected right hand synchronization but not simple reaction times. Motor anticipation was deteriorated by anodal tDCS, while cathodal tDCS yielded the reverse effect. The variability of interval reproduction was increased by anodal left M1 tDCS, whereas it was reduced by cathodal tDCS. No significant effects on simple reaction times were found. The present data support the hypothesis that left PPC is causally involved in right hand anticipatory motor control exceeding pure motor implementation as processed by M1 and possibly indicating subjective timing. Since M1 tDCS particularly affects motor implementation, the observed PPC effects are not likely to be explained by alterations of motor-cortical excitability. •Left PPC anodal tDCS deteriorates right hand motor anticipation.•Left PPC cathodal tDCS facilitates right hand motor anticipation.•These effects cannot be explained by altered excitability of the primary motor cortex.•Left PPC represents a core component for anticipatory motor control of the right hand.